The modern JavaScript bootcamp (2019) - Mead, Andrew (Packt Publishing, 2019)
"JavaScript is the most popular programming language in recent times but learning it may seem challenging without the right guidance. You may end up wasting time on out-of-date courses and incomplete YouTube tutorials that talk about JavaScript features without effectively demonstrating how to use them for building real-world applications. Sounds familiar? The Modern JavaScript Bootcamp (2019) starts with the basics and gradually builds on your knowledge of the JavaScript language. You'll not only learn the features of the language, but also how to use those features together to develop a complete application. As you progress, you'll cover modern ES6 and ES7 JavaScript features used in the real world. Next, you'll build three JavaScript applications, before going on to discovering the 80 challenges designed to help you get started with writing code, adding app features, and solving different problems. You'll then be equipped with the skills you need to launch an application, right from the first line of code through to completion. By the end of this course, you will be well-versed with JavaScript and have developed the skills you need to confidently build your own applications."--Resource description page